The Effect Of Capital Structure And Dividend Policy On Firm Value With Profitability As A Moderating Variable In Property And Real Estate Companies - Triyanita Triyanita; Herman Paleni; Yulpa Rabeta (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the effect of capital structure and dividend policy on firm value, as well as to examine the role of profitability as a moderating variable. This research employs a quantitative approach using secondary data in the form of corporate financial statements obtained from the Indonesia Stock Exchange. The analytical method used is panel data regression, with model selection conducted through the Chow test, Hausman test, and Lagrange Multiplier (LM) test, resulting in the Random Effect Model (REM) as the most appropriate model. Hypothesis testing is carried out using the t-test, F-test, coefficient of determination (R²), and Moderated Regression Analysis (MRA). The results indicate that partially, capital structure does not have a significant effect on firm value, while dividend policy has a significant effect on firm value. Simultaneously, capital structure and dividend policy do not have a significant effect on firm value. The low coefficient of determination suggests that other factors outside the model influence firm value. Furthermore, the moderation test results show that profitability is not able to moderate the effect of capital structure and dividend policy on firm value. These findings support the Pecking Order Theory, which states that firms tend to rely more on internal financing sources, as well as the Signalling Theory, which explains that dividend policy can serve as a positive signal to investors. However, the effectiveness of financial policies in increasing firm value largely depends on contextual factors and firm characteristics. Therefore, future research is recommended to include additional variables and apply more comprehensive methodological approaches.